Prevalence and associations of problematic smartphone use with smartphone activities, psychological well-being, and sleep quality in a household survey of Singapore adults. - Rebecca Hui Shan Ong; Hui Shan Sim; Manfred Max Bergman; Choon How How; Constance Ai Li Png; Chau Sian Lim; Lai Huat Peh; Hong Choon Oh (PLoS ONE)
Introduction Despite the many benefits of smartphones, researchers have raised concerns over problematic smartphone use (PSU) and its negative effects on physical and psychological well-being. Studies examining PSU and its impact among adults remain limited. Hence, we aim to examine the prevalence of PSU among adults in Singapore, and explore its associations with smartphone activities, sleep quality, and psychological well-being, as well as age and gender-related differences in these associations. Methods A household survey (n = 1200) was conducted among multi-ethnic Singapore adults aged 21 to 60. The survey employed a proportionate stratified random sampling approach. The Smartphone Addiction Scale-Short Version was used to determine risk of PSU. Adjusted multivariable logistic regressions, age-stratified (21-30, and above 30) analyses and sensitivity analyses were performed. Results The survey response rate was 45.7%. PSU prevalence rate was estimated to be 34.0%. Adults at risk were younger (OR = 3.72, p < 0.001), had poor sleep quality (OR = 2.94), reported depressive (OR = 2.84, p = 0.001) or anxiety symptoms (OR = 2.44, p < 0.001), tend to use smartphones for social media (OR = 2.81, p = 0.002) or entertainment (OR = 2.72, p < 0.001). Protective factors include higher levels of social support (OR = 0.76, p = 0.007), using smartphones for calling family (OR = 0.39, p = 0.003) and friends (OR = 0.53, p = 0.030), and spending four hours or less of smartphone usage duration (OR = 0.40, p < 0.001). Sensitivity analyses confirmed these findings. Associations between PSU and poor sleep quality (OR = 3.72, p < 0.001), depressive (OR = 3.83, p < 0.001), and anxiety symptoms (OR = 2.59, p = 0.004) and social media usage (OR = 3.46, p < 0.001) were more pronounced in adults over 30. PSU was more prevalent among females in those aged 21-30 (OR = 2.60, p = 0.022). Social support appears to be a protective factor for adults over 30 (OR = 0.64, p < 0.001) but was not observed in those aged 21-30. Among males, younger age (21-30 years), poor sleep quality, depressive symptoms, and anxiety symptoms, and using social media and entertainment apps were significantly associated with PSU. Females showed similar associations. Social support appears to be a protective factor for females (OR = 0.70, p = 0.018), but this association was not observed for males. Shorter smartphone usage times were inversely associated with PSU in both genders. Conclusion A substantial proportion of adults exhibited PSU. Findings highlight the differential associations between PSU and psychological well-being, social support, interactions with technology, and sleep quality. These associations are influenced by age which has implications for preventive efforts.